Renin-angiotensin system inhibitors can be a first choice drug for hypertension in patients treated with vascular endothelial growth factor inhibitors. (14th October 2021) - Moriyama, S; Hieda, M; Fukuda, H; Kawano, S; Yokoyama, T; Fukata, M; Kusaba, H; Maruyama, T; Baba, E; Akashi, K
Abstract: Background: Vascular endothelial growth factor Signaling Pathway (VSP) inhibitor suppresses tumor growth in solid cancers with disorganized tumor vasculature.1 However, VSP inhibitor often provokes hypertension as an adverse effect.2 The VSP inhibitor-induced hypertension may lead to a dose reduction or discontinuation of the treatment, which cause to poor prognosis. Therefore, it is important to investigate the appropriate anti-hypertensive treatment during cancer therapy. Although renin-angiotensin system (RAS) inhibitor or calcium channel blocker (CCB) is recommended to first-line anti-hypertensive drugs for cancer patients, 3 it has not been well-elucidated whether RAS inhibitor or CCB is a beneficial impact for clinical outcome. Purpose: The aim of this study is to clarify whether RAS inhibitor or CCB would be an effective drug as the first antihypertensive drug during VSP inhibitor therapy. Method: From the LIFE Study database which consisted of 14 municipality-level information from claims data between 2016 and 2020, 1, 263 cancer patients treated with VSP inhibitors were retrospectively reviewed. All patients were stratified into two groups according to hypertensive drugs: (1) RAS inhibitors alone (n=512) and (2) CCBs alone (n=751) (Figure 1). The time to treatment failure (TTF) was substituted as an alternative clinical indicator of overall survival. The Kaplan-Meier survival method with the log-rank test was conducted to compare the TTF between the two groups. In addition, Cox proportional hazard model adjusted with baseline clinical characteristics was performed to analyze determinant factors for TTF. Results: There were no difference in baseline characteristics including age, sex, primary cancer site, the type of VSP inhibitors, and past medical histories between the two groups, excepted for renal failure. The rate of renal failure was significantly higher in the RAS inhibitor group than in the CCB group (p=0.013). TTF in the patients treated with RAS inhibitors were significantly longer than that with CCB (median TTF [25th–75th percentile]: 183 [61–455] vs. 153 [61–351] days, p=0.020) (Figure 2). In Cox proportional hazard analysis adjusted with age, sex, past medical history, primary cancer lesion, and type of VSP inhibitors, RAS inhibitor was a significantly independent favorable factor to TTF, compared to CCB (Hazard ratio 0.86, 95% confidence interval [0.77–0.97], p=0.011). Conclusion: RAS inhibitor is associated with a favorable clinical outcome than CCB, and can be a first choice for treating hypertension during cancer therapy with VSP inhibitors. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Japan Society for the Promotion of Science (JSPS) Grants-in-Aid for Scientific Research (KAKENHI)